Measures Undertaken for the Management of Obstructive Uropathy in Advanced Carcinoma Cervix (Bangladesh Journal of Urology, 2020)
Objectives: To find out the procedures adopted for the management of obstructive Uropathy in advanced Carcinoma cervix and To identify the most excellent option for their management.Methods: It was a retrospective cross sectional study. Data were collected from patient’s record of Urology outpatient department (OPD) and indoor of Dhaka Medical College Hospital (DMCH) for the year 2010. Patients attended with other causes of obstructive uropathy were excluded.Results: Total 32 patients were included in this study. Mean age of the patients was 46±6.90 years. All of them were squamous cell carcinoma of stage III & IV disease. About 60% patients received pre-operative radiotherapy for cervical cancer. Twenty three patients underwent retrograde ureteral stenting, 6 patients underwent percutaneous nephrostomy (PCN) and rest 3 underwent cutaneous ureterostomy. Mean pre-operative serum creatinin was 2.68±.24 mg/dl. and post-operatively it dropped to 1.30±.05 mg/dl. which is statistically very much significant. Post-operative hydronephrosis also improved significantly following operations. Difference observed in the improvement of renal function or hydronephrosis among the surgical procedures but it was not statistically significant.Conclusion: Any of the surgical procedures undertaken for the management of obstructive uropathy due to advanced carcinoma of cervix, provided significant improvement of renal function and hydronephrosis.Bangladesh Journal of Urology, Vol. 15, No. 1, Jan 2012 p.15-17